C-Myc Signaling Pathway in Treatment and Prevention of Brain Tumors - Ashrafizadeh, Milad; Zarabi, Ali; Hushmandi, Kiavash; Moghadam, Ebrahim R.; Hashemi, Farid; Daneshi, Salman; Hashemi, Fardin; Tavakol, Shima; Mohammadinejad, Reza; Najafi, Masoud; Dudha, Namrata; Garg, Manoj (Current Cancer Drug Targets, 2021)
Brain tumors are responsible for high morbidity and mortality worldwide. Several factors such as the presence of blood-brain barrier (BBB), sensitive location in the brain, and unique biological features challenge the treatment of brain tumors. The conventional drugs are no longer effective in the treatment of brain tumors, and scientists are trying to find novel therapeutics for brain tumors. In this way, identification of molecular pathways can facilitate finding an effective treatment. c-Myc is an oncogene signaling pathway capable of regulation of biological processes such as apoptotic cell death, proliferation, survival, differentiation, and so on. These pleiotropic effects of c-Myc have resulted in much fascination with its role in different cancers, particularly brain tumors. In the present review, we aim to demonstrate the upstream and down-stream mediators of c-Myc in brain tumors such as glioma, glioblastoma, astrocytoma, and medulloblastoma. The capacity of c-Myc as a prognostic factor in brain tumors will be investigated. Our goal is to define an axis in which the c-Myc signaling pathway plays a crucial role and to provide direction for therapeutic targeting in these signaling networks in brain tumors.
Keywords: glioma